Efektivitas Kombinasi Media Tanam dan Pupuk NPK dalam Mendukung Pertumbuhan dan Hasil Terong Ungu (Solanum melongena L.) - Rian Fausan; Fandi Ahmad; Hayatuidn Hayatudin (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2025)
This study aims to determine the effect of the interaction between the composition of planting media and the dose of NPK Mutiara 16-16-16 fertilizer on the growth and yield of purple eggplant (Solanum melongena L.). The study used a factorial randomized block design (RBD) with a combination of several planting media (soil, coffee husks, and chicken manure) and different doses of NPK fertilizer. The parameters observed included plant height, number of leaves, stem diameter, root volume, number of fruits, and fruit weight. The results showed a significant interaction between planting media and NPK fertilizer doses on all growth and yield parameters. The best treatment was obtained in the M3 planting media (1 kg soil: 1 kg coffee husks: 2 kg chicken manure = 1:1:2) with a dose of P2 fertilizer (10 g/polybag or equivalent to 350 kg/ha) which resulted in a plant height of 66.73 cm, more leaves, larger stem diameter, the highest root volume (86.67 ml), optimal number of fruits (2.00 fruits), and the most significant fruit weight (0.40 kg). In contrast, the control treatment (without fertilizer) resulted in lower growth and yield. It can be concluded that the combination of chicken manure and NPK Mutiara 16-16-16 fertilizer at a dose of 10 g per polybag can increase the vegetative and generative growth of purple eggplant plants.